Do developmental differences in mental toughness exist between specialized and invested Australian footballers? - Gucciardi, Daniel (Elsevier Sciences Ltd, 2009)
Using a cross-sectional design, the primary purpose of the present study was to examine developmental differences in mental toughness between specialized and invested Australian footballers. A secondary purpose was to examine the psychometric properties of the Australian football Mental Toughness Inventory (AfMTI; Gucciardi, Gordon, & Dimmock, 2009a) with a sample of youth footballers. Participants were 350 footballers aged between 13 and 18 (M = 15.88; SD = 1.71); 144 (Mage = 14.06; SD = .89) and 206 (Mage = 17.02; SD = 1.06) footballers from the specialized and investment developmental stages, respectively. A confirmatory factor analysis of the AfMTI using AMOS did not reveal support for its psychometric structure; however, a revised version received support. A MANOVA revealed the presence of a significant difference between the two developmental groups, and follow-up ANOVA’s indicated that the desire success and sport awareness subscales contributed to multivariate effect. It appears that developmental differences should be considered in future theorizing on the development of mental toughness.